Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Notes: Decomposing Fractional Functions With Linear Factors ONLY Into Partial Fractions

Download as doc, pdf, or txt
Download as doc, pdf, or txt
You are on page 1of 7

Notes

PARTIAL FRACTIONS

Consider a function such as f(x) ≡ 2 + x


2
x+1 x +1

the function maybe expressed as a single fraction with a common denominator.

Thus f(x) ≡ 2 + x ≡ 2(x2 + 1) + x(x + 1)


x+1 x2 + 1 (x + 1 ) (x2 + 1)

≡ 2x2 + 2 + x2 + x ≡ 3x2 + x + 2
(x + 1 ) (x2 + 1) (x + 1 ) (x2 + 1)

It is often useful to be able to reverse this operation i.e. to say that take the function such
as

f(x) ≡ x–2
(x + 3 ) (x – 4)

And express f(x) as the SUM of TWO (or in some cases MORE THAN TWO) separate
fractions.

This process is called Decomposing or expressing a function in partial fractions.

 NB – If the original fractional function is ‘Proper’ then so too will be the


separate/Partial fractions.

Decomposing fractional functions with linear factors ONLY into Partial fractions.

Example 1. Decompose x+2 into Partial fractions.


(x – 2) (x + 4)

 NB – Since the fraction/or fractional function is ‘proper’ then so too will be the
partial fractions.

x+3 ≡ A + B
(x – 2) (x + 4) (x – 2) (x + 4)

x+3 ≡ A(x + 4) + B(x – 2)


(x – 2) (x + 4) (x– 2 ) (x + 4)

Now since the denominator are obviously identical the numerator MUST also be
identical.
Notes

i.e. x + 3 ≡ A(x + 4) + B(x – 2 )

 NB – The L.H.S = R.H.S. for any value of x

To eliminate B one MUST choose 2 as the value for x.

x + 3 ≡ A(x + 4) + B(x – 2)

2 + 3 = A(2 + 4) + B(2 – 2)

5 = A(6) + B(0)

5 = A+0
6
A= 5
6

To eliminate A one MUST choose –4 as the value for x.

x + 3 ≡ A(x + 4) + B(x – 2)

–4 + 3 = A(–4 + 4) + B(–4 – 2)

– 1 = A(0) + B(–6)

–1 = B
–6
B = 1
6

.
. . x+3 ≡ A + B
(x – 2) (x + 4) x–2 x+4

≡ 5 1 + 1 1
6 x–2 6 x+4

x+3 ≡ 5 + 1
(x– 2) (x + 4) 6(x – 2) 6(x + 4)

Example 2. Express x2 – 3 in partial fractions.


2
(x – 1) (x + 1)

The denominator of the fractional functions contains a quadratic factor i.e. x2 + 1.


Notes

x2 – 3 ≡ A + Bx + C
(x – 1) (x2 + 1) x–1 x2 + 1

Choose the numerators on the R.H.S. so that each partial fraction is ‘proper’.

x2 – 3 ≡ A(x2 + 1) + (Bx + C)(x – 1)


(x – 1) (x + 4) (x – 1) ( x2 + 1)

x2 – 3 ≡ A(x2 + 1) + (Bx + C)(x – 1)

To eliminate B and C by substituting in 1 as the value for x.

x2 – 3 ≡ A(x2 + 1) + (Bx + C)(x – 1)

(1)2 – 3 = A[(1)2 + 1 ] + [B(1) + C] [(1) – 1]

1 – 3 = A[1 + 1] + [B(1) + C] [ 1 – 1]

– 2 = A(2 ) + (B + C) (0)

– 2 = 2A

– 2 = 2A
2 2

–1 = A .... [1]

* NB – There is absolutely no value which one can substitute for x to eliminate A,


(as there is no value of x for which x2 + 1 = 0).

But by substituting in 0 for x will eliminate B giving

(0)2 – 3 = A[(0)2 + 1 ] + [B(0) + C] [(0) – 1]

Since A = – 1 from [1]

– 3 = (– 1) (1) + (C) (–1)

– 3 = ( – l ) + (C)(– 1)

–3 = –1–C

C = 3 –1

C= 2 ….[2]
Notes

To eliminate B by substituting in 1 as the value for x.

x2 – 3 ≡ A(x2 + 1) + (Bx + C)(x – 1)

Solve or B by substituting in 2 for x

(2)2 – 3 = A[(2)2 + 1] + [ 2B + C][(2) – 1]

4 – 3 = A[4 + 1] + [ 2B + C][1]

4 – 3 = 5A + 2B + C

Since A = – 1 and C = 2 from [1] and [2] then

4 – 3 = 5A + 2B + C

1 = 5(– 1) + 2B + (2)

1 = –5 + 2B + 2

4 = 2B
.
. . 4 = B =2
2

.
. . x ≡ A + Bx + C ≡ – 1 + 2x + 2
2
(x – 1) (x + 1) x–1 x2 + 1 x–1 x2 + 1

Example 3. Express x–1 in partial fractions.


(x + 1) (x – 2) 2

Since (x – 2) 2 ≡ (x – 2) (x – 2)

However (x – 2)2 is what one would call a repeated factor, but it is also quadratic in its
nature.

One maybe tempted to initially think of using the partial fraction form of :

x–1 as A + Bx + C
2
(x + 1) (x – 2) (x + 1) (x – 2)2

 NB – However THIS IS NOT THE SIMPLEST Partial Fraction.


If one were to consider solely the fraction
Notes

Bx + C and let C = – 2B + D
(x – 2)2

Then Bx + C ≡ Bx – 2B + D
(x – 2)2 (x – 2)2

= B(x – 2) + D
(x – 2)2 (x – 2)2

= B + D
x–2 (x – 2)2

In general any Repeated factor of the form (ax + b)2 in the denominator
will give rise to TWO partial fractions of the form:

A and B
ax + b (ax + b)2

* NB – A Repeated factor (ax + b)3 will give rise to THREE partial fractions of the form

A B and C
ax + b (ax + b)2 (ax + b)3

With all of that above being considered one can now solve the original question.

x–1 ≡ A + B + D
(x + 1) (x – 2) 2 x + 1 x–2 (x – 2)2

Since (x – 2) 2 ≡ A(x – 2)2 + B(x + 1)(x – 2) + D(x + 1)

Eliminate A and B by substituting 2 for x

2 – 1 = A(2 – 2)2 + B(2 + 1) (2 – 2) + D(2 + 1)


1 = A(0)2 + B(3) (0) + D(3)
1 = D(3)
⅓= D

Eliminate D and B by substituting –1 for x

– 1– 1 = A(– 1– 2)2 + B(– 1+ 1) (– 1– 2) + D(– 1 + 1)


– 2 = A(– 3)2 + B( 0) (– 3) + D(0)
– 2 = 9A
–2 =A
9
Notes

.
. . x–1 ≡ – 2 + 2 + 1
(x + 1) (x – 2) 2 9x + 1 9(x – 2) 3(x – 2)2

Express x3 in partial fractions


(x + 1)(x – 3)

Since this functions numerator is larger in terms of degree/order than the denominator it
is an improper fractional function.

With this being stated fact, it is necessary first to divide the numerator by the
denominator so as to obtain a MIXED FRACTION.

x+2
2 3
x – 2x – 3 x x3/ x2 = x, then x(x2 – 2x – 3)
– ( x3 – 2x2 – 3x )
2x2 + 3x 2x2 / x2 = 2, then 2(x2 – 2x – 3)
– (2x2 – 4x – 6)
7x + 6 Remainder

 NB – It is not necessary to go further as the remainders order/degree of 1 is less


than that of the divisor – which in this instance is 2.

x3 ≡ x + 2 + Remainder
(x + 1) (x – 3) (x + 1) (x – 3)

≡ x + 2 + A + B
x+1 x–3

.
. . x3 ≡ (x + 2) (x + 1) (x – 3) + A(x – 3) + B(x + 1)

Eliminate A by substituting in 3 for x

(3)3 ≡ (3+ 2) (3 + 1) (3 – 3) + A(3 – 3) + B(3 + 1)


27 = (5) (4) (0) + A(0) + B(4)
27 = 4B
27 = B
4
Eliminate B by substituting in –1 for x

(–1)3 = (–1 + 2) (–1 + 1) (–1 – 3) + A(–1 – 3) + B(–1 + 1)


–1 = (1) (0) (–4) + A(–4) + B(0)
–1 = –4A
¼ =A
Notes

.
. . x3 ≡ x+ 2 + 1 + 27
(x + 2)(x – 3) 4(x + 1) 4( x – 3)

You might also like